2022
DOI: 10.1155/2022/3505228
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Effect Analysis of Nursing Method Based on Stratified Emergency Knowledge in Emergency Myocardial Infarction

Abstract: First aid is to give immediate first aid to patients who have suffered accidental injuries or sudden diseases before the emergency medical personnel arrive at the scene or are sent to the hospital for treatment; myocardial infarction is a severe and emergency of coronary heart disease. It is often because of coronary atherosclerosis, plaque rupture, bleeding, or thrombosis, which leads to the acute and complete occlusion of the coronary arteries and acute necrosis of the myocardium. This article aims to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%